Respuesta :
x^2 + 2x = -2
x^2 + 2x + 2 = 0
[tex]x= \frac{-b\pm \sqrt{b^2-4ac} }{2a} \\x=\frac{-2\pm \sqrt{2^2-(4\times1\times2)} }{2\times1}\\x=\frac{-2\pm \sqrt{4-8} }{2}\\x=\frac{-2\pm \sqrt{-4} }{2}\\x=\frac{-2\pm2i }{2}\\x=-1\pm i[/tex]
Therefore, x = -1 + i or x = -1 - i
Therefore, the correct answer is the third option.
x^2 + 2x + 2 = 0
[tex]x= \frac{-b\pm \sqrt{b^2-4ac} }{2a} \\x=\frac{-2\pm \sqrt{2^2-(4\times1\times2)} }{2\times1}\\x=\frac{-2\pm \sqrt{4-8} }{2}\\x=\frac{-2\pm \sqrt{-4} }{2}\\x=\frac{-2\pm2i }{2}\\x=-1\pm i[/tex]
Therefore, x = -1 + i or x = -1 - i
Therefore, the correct answer is the third option.